A work study on Mareska Enterprises - Bernarte, Alfredo L. Jr (College of Engineering, 1996)
The company under study is Mareska Enterprises. It manufactures a variety of table and wall decor. The group chose to conduct a study on the manufacture of a particular product, the letter key holder. The group identified as the company's problem areas the following : inability to meet deadlines, undefined daily schedule, undefined division of tasks, and undefined work hours. The group has limited itself to studying the product from the time the pre-cut wood arrives in the general work area in Cubao until the final assembly part of the process. The group was limited by the fact that the product under study is not the only one being processed in a single day. The group further limited itself to measuring the time it takes painting and gold taping procedures to finish. The following recommendations are presented by the group : (1) a proposed layout, (2) cleanliness policies, (3) improvements in work conditions and organization, (4) expected output for a given number of hours, (5) an operations manual, (6) an order form, (7) a delivery form and (8) a modified sales invoice form.